KONDISI FISIK ATLET LEMPAR CAKRAM (DISCUS THROW) PUSAT LATIHAN NASIOANAL B DI SURABAYA - Wulandari, Fifit Yeti (Universitas Negeri Surabaya, 2021)
Discus throwing really requires good physical condition, especially in discus throwing, it requires flexibility and explosive power and other physical components. Not only explosive power, other physical conditions play a very significant role in discus throwing, including strength, speed, endurance, flexibility, coordination and balance. This research is a quantitative research with an ex-post facto descriptive approach. In this study, the focus was on the physical condition of the PLATNAS B Discus Throwing athletic athletes. The subjects of this study were 4 PLATNAS B Discus Throwing athletes consisting of 3 men and 1 woman. Based on the results of the research, it was concluded that the physical component of the speed of the PLATNAS B Discus Throwing athletes obtained